2000
DOI: 10.4049/jimmunol.164.7.3494
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide Decreases Expression of HLA-DR and CD86 by Human Dendritic Cells and Dampens Dendritic Cell-Driven T Cell-Proliferative Responses Via the Type I Calcitonin Gene-Related Peptide Receptor

Abstract: These studies were performed to establish whether functional receptors for calcitonin gene-related peptide (CGRP) are present on human dendritic cells (DCs) and to investigate potential immunomodulatory effects of CGRP on DCs other than Langerhans cells. Reverse transcriptase-PCR revealed expression of mRNA for a type 1 CGRP receptor by mature and immature blood-derived DCs. Sequence analysis confirmed the identity of the type 1 CGRP receptor (CGRP-R1). Addition of CGRP (10−7 M) to mature and immature DCs resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 26 publications
(27 reference statements)
8
38
0
Order By: Relevance
“…The main effect of CGRP administration both in vitro and in vivo is to dampen the immune response essentially by affecting antigen presentation in a variety of APCs such as Langerhans cells, dendritic cells, monocytes, and macrophages. 32,33,53,55,56 Our results on the functional effect of the autocrine synthesis of CGRP in monocytes indicate that the control of MHC class II and B7 costimulatory molecules is indeed a key feature of the biologic action of CGRP.As previously demonstrated, LPS stimulation strongly upregulates B7.1 (CD80) in adherent monocytes, 57 whereas B7.2 (CD86), which is constitutively expressed, is down-regulated by LPS 58,59 as well as HLA-DR. 48 In our study we show for the first time that the described LPS-induced reduction in CD86 and HLA-DR expression in human monocytes 48,58,60 is mediated by the LPS-induced synthesis of NGF and CGRP. Our data show that in LPS-activated monocytes, the neutralization of endogenous NGF, by reducing the synthesis of CGRP, up-regulates CD86 but does not modify CD80 expression.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The main effect of CGRP administration both in vitro and in vivo is to dampen the immune response essentially by affecting antigen presentation in a variety of APCs such as Langerhans cells, dendritic cells, monocytes, and macrophages. 32,33,53,55,56 Our results on the functional effect of the autocrine synthesis of CGRP in monocytes indicate that the control of MHC class II and B7 costimulatory molecules is indeed a key feature of the biologic action of CGRP.As previously demonstrated, LPS stimulation strongly upregulates B7.1 (CD80) in adherent monocytes, 57 whereas B7.2 (CD86), which is constitutively expressed, is down-regulated by LPS 58,59 as well as HLA-DR. 48 In our study we show for the first time that the described LPS-induced reduction in CD86 and HLA-DR expression in human monocytes 48,58,60 is mediated by the LPS-induced synthesis of NGF and CGRP. Our data show that in LPS-activated monocytes, the neutralization of endogenous NGF, by reducing the synthesis of CGRP, up-regulates CD86 but does not modify CD80 expression.…”
supporting
confidence: 53%
“…Complementary to this observation are the findings showing that the administration of exogenous CGRP to monocyte-derived dendritic cells decreased HLA-DR expression and inhibited T-cell proliferative response. 56 Furthermore, in septic patients characterized by decreased MHC class II molecule expression in monocytes, 70,71 CGRP plasma levels are greatly enhanced and the highest levels are associated with a lethal outcome. 72 These findings, together with our in vitro data, suggest that CGRP could be a key mediator of the LPS-induced responses.…”
mentioning
confidence: 99%
“…Here, ADM2 was demonstrated to inhibit MHCII expression in adipocytes primarily through CRLR/RAMP1, which is the classical pharmacological CGRP 1 receptor (45). In agreement with our present findings, some reports have shown that CGRP reduced MHCII expression in dendritic cells and hair follicle dermal papilla (46,47), although the exact mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Further, to understand human skin diseases, it is important to consider the possibility that neurotransmitter concentration is controlled by a patient's mental condition and that an Ag can have a direct effect on the nervous system. In fact, CGRP treatment inhibits Ag presentation by human peripheral mononuclear cells and human DCs (47,48). Determination of the mechanisms underlying CGRP-mediated immune regulation will open up a new avenue for understanding various types of skin inflammation and skin diseases.…”
Section: Discussionmentioning
confidence: 99%